Mucocutaneous manifestations in patients with chronic kidney disease: a cross-sectional hospital-based study from North-East India - Hitesh S Khatri; Pankaj Adhicari; Manzoor A Parry; Manjuri Sharma (Wolters Kluwer Medknow Publications, 2022)
Background Cutaneous manifestations in chronic kidney disease (CKD) can affect quality of life and can vary across regions, races, and nutritional status of patients. Objective To study the prevalence of mucocutaneous manifestations in patients with CKD and compare between dialysis and nondialysis patients. Patients and methods This was a cross-sectional study from North-East India. A total of 210 patients with CKD were included, with 61 patients in dialysis group and 149 in the nondialysis group. A comprehensive history, detailed examination, and all the relevant investigations were done. Results There was a male predominance in this study, and the mean age was 49.85±12.5 years. Diabetes mellitus (42.9%) was the most common cause of CKD. Cutaneous involvement was seen in 142 (67.61%) patients, with predominance in dialysis patients (60/61) (98.36%) as compared with nondialysis patients (80/149) (55.03%). Xerosis (58.09%) was the most common skin change seen in 122 patients, being more in the dialysis group as compared with the nondialysis group (73.8 vs. 51.7%; P=0.0034). This was followed by pallor (36.19%) of the skin and mucosa. Pruritus (35.23%) was seen in 74 patients, being more in dialysis patients. Cutaneous infections were seen in 57 patients. Absent lunula (14.26%) and half-and-half nail (12.85%) were the most common nail changes. Mucosal changes were seen in 28 (13.33%) patients. Hair changes were seen in 16.67% of patients, with predominant affection in dialysis patients. Conclusion Xerosis, pruritus, skin pallor, absent lunula, xerostomia, macroglossia, and infections were the most common mucocutaneous manifestations in this study. Xerosis, pruritus, absent lunula, and hair changes were more common in dialysis patients.